Lung function parameters among Australian Aboriginal 'apparently healthy' adults: an Australian Caucasian and Global Lung Function Initiative (GLI-2012) various ethnic norms comparative study. (3rd June 2021) - Heraganahally, Subash S.; Howarth, Timothy; White, Elisha; Sorger, Lisa; Biancardi, Edwina; Ben Saad, Helmi
ABSTRACT: Background : There is sparse literature evidence evaluating the applicability of the GLI-2012 spirometric norms for Australian Aboriginal adults. Methods : Lung function parameters (LFPs) were compared between Australian Aboriginal and Australian Caucasians, and the fit of Australian Aboriginals LFPs with various ethnic GLI equations was tested. Results : Of 1350 and 5634 Pulmonary function tests (PFTs) in Australian Aboriginal and Australian Caucasian adults, 153 and 208 PFTs matched for anthropometrics and normal chest radiology, respectively. Absolute FVC and FEV1 values were 20% lower in Australian Aboriginals compared to Australian Caucasians. Differences remained significant after accounting for age, sex, height, weight and smoking status in multivariate regression (FVC −0.84 L (−0.98, −0.71), FEV1 − 0.72 L (−0.84, −0.59), but with nearly preserved FEV1 /FVC. GLI-2012 transformation resulted in z-scores significantly below zero for each of FVC, FEV1 and FEV1 /FVC with z-scores ranging from −4.52 (−4.87, −4.16) for North East Asian FVC transformation for males, to −0.34 (−0.73, 0.05) for Black FVC transformation for females. Conclusions : Australian Aboriginal adults had 20% lower values for FVC and FEV1 but nearly preserved absolute FEV1 /FVC in comparison to Australian Caucasians. The GLI-2012 spirometric norms do not appear to fit for Australian Aboriginal adults regardless of which ethnicity options selected, including 'others/mixed'.